Tipificação dos agricultores familiares do agreste do estado da Paraíba segundo a modernização - Abreu, Tatiana Losano de (2013)
The overall objective is to typify the family farm establishments in Meso Wasterland of Paraíba, according to the pattern of modernization . Beyond this general goal, we intend to achieve the following specific objectives : to draw a profile of family farming in Wasterland of Paraíba; discuss the process of agricultural modernization in Paraíba and Wasterland of Paraíba, and study the importance of public policies in this modernization process, particularly credit policies and technical assistance. To achieve the stated objectives, the following methodological procedures were adopted: a) literature research, b) survey of census data that were used to characterize the rural family production in Wasterland of Paraíba, c) application of Item Response Theory (IRT) on the data collected through direct research on 314 establishments family farms that represent the specificities of the eight microregions of Wasterlamd of Paraíba. The results of the application of IRT allow us to state that most of the farmers of Wasterland of Paraíba can still be considered subsistence farmers though with levels of differentiation according to the degree of modernization. Public policies have played an important role in this process.